Women’s Burden of Caring for Orphans: The bio-psychosocial and economic challenges for caregivers in a rural community in South Africa - Dube, Misheck (Technium Social Sciences Journal, 2021)
The practical activity of orphan-care in Social Work has received unquestionable and resounding globally attention. However, the skewed care of orphans towards women and its associated bio-psychosocial and economic challenges in the rural communities deserves special investigation and analysis. This article discusses women’s burden of orphan-care and associated bio-psychosocial and economic challenges experienced by carers in Alice in the Eastern Cape Province in South Africa. Using a qualitative research approach and voluntary purposive sampling to ensure that carers of orphans were engaged in the study, individual face-to-face interviews were conducted to engage twenty caregivers. Data were analysed thematically and backed by existing literature. The findings showed that women caregivers of orphans experienced a plethora of bio-psychosocial and economic issues when caring for orphans in the rural communities. The article makes relevant recommendations for the profession of Social Work and stakeholders of orphan-care.